Aligning Financial Systems to Meet the Needs of Citizens and Enterprises - Karl-Peter Schackmann-Fallis; Sonja Scheffler (Vierteljahrshefte zur Wirtschaftsforschung, 2017)
The European Commission's current initiative to commence consultations on the action plan to build a Capital Markets Union is to be welcomed. The objective must be to create a stable and sustainable financial system, providing all households and companies with appropriate access to financial services. Measures implemented in connection with the aspired-to Capital Markets Union must in no way weaken the classic bank loan and bypass the needs of companies. What is important in the first instance is a critical review of existing financial market regulation. The objective should be an integrated regulatory framework, avoiding regulatory duplication and inconsistencies, while taking account of cross-references to the respective regulations. – – Der aktuelle Antritt der Europäischen Kommission, den Aktionsplan zur Kapitalmarktunion zu überprüfen, ist zu begrüßen. Das Ziel muss es sein, ein stabiles und nachhaltiges Finanzsystem zu schaffen, das allen Haushalten und Unternehmen angemessenen Zugang zu Finanzdienstleistungen gewährt. Die Maßnahmen der Kapitalmarktunion dürfen keinesfalls den Bankkredit an den Bedürfnissen der Unternehmen vorbei schwächen. Wichtig ist zunächst eine Überprüfung der bestehenden Finanzmarktregulierung. Ziel sollte ein Regelungsgefüge aus einem Guss sein, das Doppelregulierungen und Inkonsistenzen vermeidet und die Querbezüge zu den jeweiligen Regulierungen berücksichtigt.
Keywords: D14; G2; G3; R51; 330; Bank-based system; bank lending; capital market; corporate financing; decentralized financial institutions; economic development; financial industry; financial market regulation; household saving; market-based system; proportionality